Taxonomic revision and zoogeographical patterns of the species of Gnopharmia Staudinger, 1892 (Geometridae, Ennominae) - Sh., Hossein Rajaei; Stüning, Dieter; Trusch, Robert (Zootaxa, 2012)
The genus Gnopharmia Staudinger, 1892 is revised, based on more than 2000 specimens from the entire area ofdistribution and study of type material of all described taxa, as far asmap available. Seven species and three subspeciesare confirmed as valid for the genus. All important morphological characters have been studied and compared, includingmale and female genitalia. In addition, preliminary results of DNA-Barcoding were used to reassess our taxonomicdecisions, based on morphological studies. Type specimens and their labels are illustrated and additional specimens,demonstrating the variability of certain species, are also figured. Male genitalia of all valid species are figured and SEMphotos of the aedeagus are illustrated. Further important structures, the so-called ‘octavals’ on the male pre-genitalabdomen, are also figured. Female genitalia revealed a high similarity between species, combined with a considerablevariability, and were unsuitable for characterisation of species. Female genitalia of three species are figured to exemplifythis situation. As a result of the morphological and genetic studies, 12 out of the 21 described species and subspecies aresynonymised or transferred to the closely related genus Neognopharmia Wehrli, 1953. In addition, G. colchidariacocandaria (Erschoff, 1874) is revived as a valid species, G. sinesefida Wehrli, 1941 is downgraded to a subspecies of G.colchidaria Lederer, 1870. Five new records for the fauna of the following countries are presented: G. colchidariaobjectaria: new for Pakistan; G. irakensis: new for Turkey and Pakistan; G. kasrunensis: new for Oman and G. sarobiana: new for Pakistan. Distribution maps and an identification key are given for all species.